2006
DOI: 10.1027/1015-5759.22.2.85
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Cultural Equivalence of Parental Rearing Measure: EMBU-C

Abstract: We examined the cross-cultural equivalence of a widely used instrument that assesses perceived parental rearing, the EMBU-C, among native Dutch and immigrant adolescents living in The Netherlands. The results of a multigroup confirmatory factor analysis indicated that the factor structure of the EMBU-C, consisting of three latent factors (Warmth, Rejection, and Overprotection), and reliabilities of these scales are similar in both samples. These findings lend further support for the factorial and construct val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 36 publications
3
39
0
2
Order By: Relevance
“…A related issue is that the study relied on self-report data. Of note, research has shown that individuals are accurate reporters of their own behaviors (Deković et al 2006). However, it would be useful for future studies to replicate the study findings with research using other types of methodology.…”
Section: Discussionmentioning
confidence: 98%
“…A related issue is that the study relied on self-report data. Of note, research has shown that individuals are accurate reporters of their own behaviors (Deković et al 2006). However, it would be useful for future studies to replicate the study findings with research using other types of methodology.…”
Section: Discussionmentioning
confidence: 98%
“…The α level for testing nested models with the scaled chi-square difference (Bryant & Satorra, 2012) was set at .01 (e.g., Dekovic, et al, 2006;Ferrando, 2000;Gomez, 2013) for Type I error control (Green & Babyak, 1997).…”
Section: Measurement Invariance Of Odd Dimensions In Preschoolersmentioning
confidence: 99%
“…Adolescents provided the reports of their media use and self-competence. However, it is important to note that research has shown that youth are accurate reporters of their own behaviors (Dekovic, et al, 2006). Nonetheless, it would be informative for future research to replicate the findings from this study using other types of methodology (e.g., parent reports).…”
Section: Discussionmentioning
confidence: 86%